Space in ancient Greek literature : studies in ancient Greek narrative - Jong, Irene J. F. de. (Mnemosyne, Supplements, 2012)
This is the third volume in the series Studies in Ancient Greek narrative. It deals with the narratological category of space: how is space, including objects which function as 'props', presented in Greek narrative texts and what are its functions (thematic, symbolic, psychologising, or characterising)?How are longer descriptions organised and integrated into the story? Long deemed a mere ancilla narrationis, especially in narratives which precede the age of the realist novel, space turns out to play an important and multifaceted role in Greek literature.